Feasibility and Sensitivity Study of Big Chilli Farm Business in Jember Regency - Muhammad Firdaus; Suherman; Farid Wahyudi; Ahmad Sauqi; Nanda Widaninggar (Nusantara Science and Technology Proceedings)
This study aims to determine the feasibility and sensitivity of big chili farm business in Jember Regency. Chili is one of the horticultural plants that have high economic value, in spite of chili farm business also has a high risk, since the price of the chili was involatile. Using the case study type of research, primary data were obtained from 120 respondents of big chilli farmers in Wuluhan and Ambulu Districts. Sampling was done by the Multistage Cluster Sampling Method. Data analysis used R/C Ratio analysis and sensitivity analysis. The results showed that: 1) Big chilli farmbusiness in Jember Regency had an R/C Ratio of 3.37, so this farm business is feasible to be cultivated; 2) Big chilli farmbusiness had no loss if the maximum production cost increase was less than 237%, ceteris paribus. Likewise, a decrease in production or a decrease in selling prices up to 70.29%. This finding could be additional information to enlarge farmer’s big chili business.